Stent thrombosis in patients with chronic kidney disease. (May 2012) - Donahue, Michael; Briguori, Carlo
Chronic kidney disease is a strong predictor of adverse cardiac events, including death, myocardial infarction and stent thrombosis (ST), after percutaneous coronary intervention. In the past few years, the development of new therapeutic strategies (including both drugs and devices) and a more complete understanding of the pathophysiology and predictive factors of thrombosis have led to a significant reduction of this complication. Despite this, ST still remains a dramatic event due to its morbidity and mortality. Further efforts should be pursued to identify patients at high risk of ST in order to adopt a more effective preventive strategy. This review sought to examine the total weight of evidence regarding ST with the use of drug-eluting stents in patients with chronic kidney disease.